MODIFIKASI ALAT TANGKAP RAJUNGAN (Portunus pelagicus) DALAM MENINGKATKAN HASIL TANGKAPAN NELAYAN - Irnawati, Irnawati; Yanto, Subari; Jamaluddin P, Jamaluddin P (Jurnal Pendidikan Teknologi Pertanian, 2017)
This study aimed to modify the crab’s fishing device (Portunus pelagicus) in increasing the production of the fisherman. The number of fishing tools was 10 pieces, consists of 5 tools after the modification and 5 tools beforer the modification. This research is a design building. The data was collected through descriptive analysis and comparison analysis. The result of the research stage showed that on the first trip the highest number of catches crab is 10 tails and the second trip the highest number of catches crab is 7 tails, while the highest production of crab during 2 trip is 627 g.